Study guides

☆☆

Q: What is the discriminant of this equation 8x2 plus 5x plus 6 equals 0?

Write your answer...

Submit

Still have questions?

Related questions

(-2)2-4*8*8 = -252 The discriminant is less than zero so there's no solution to the quadratic equation.

8x2 + 16x + 8 = 0

x=5

15 = 8x2 - 14x; whence, 8x2 - 14x - 15 = (2x - 5)(4x + 3) = 0. Therefore, x = 5/2 or -3/4.

8x2 + 2x - 1 = 8x2 + 4x - 2x - 1 = 4x(2x + 1) - 1(2x + 1) = (4x - 1)(2x + 1)

16.

There is no equals sign visible but, taking the equation to be8x2 + 2x + 1 = 0,the solutions are the complex conjugate pair, -1.25 Â± 0.330719*i where i is the imaginary square root of -1.

8x2 + 16x + 8 = 8*(x2 + 2x + 1) = 8*(x + 1)2

You can multiply 8x2 or if you can put addition into the equation you can do (3+5)x2! If you need proof here it is 8x2 can be shown as 8+8 Which equals 16.

(4x + 3)(2x - 1) so x = -0.75 or 0.5

-4x2 - 32x + x + 8 = 8x2 - 56x : simplify and group the various terms-32x + 56x + x + 8 = 8x2 + 4x225x + 8 = 12x2 : Now present this as a standard quadratic equation.12x2 - 25x - 8 = 0 : Solving for the roots of a quadratic equation gives :-x = [25 ± √(252 + 4x12x8)] ÷ 2x12 = [25 ± √1009] ÷ 24 = [25 ± 31.765] ÷ 24x = 56.765/24 = 2.365 and x = -6.765/24 = -0.282x = 2.365 and -0.282

Please do not remove this question from Inappropriate or split any alts from it. Thanks!

8x2 + 6x - 9 = (2x + 3)*(4x - 3)

8x2 + 2x - 1 = (4x - 1)(2x + 1).

10x3 + 3x2

8x2 + 15 + 26x = 8x2 + 26x + 15 = 8x2 + 20x + 6x + 15 = 4x(2x + 5) + 3(2x + 5) = (2x + 5)(4x + 3)

7Improved Answer:8x2-18x+9 = (4x-3)(2x-3)

8x2+6x-35 = (2x+5)(4x-7) when factored

What are the factors? 2x3 - 8x2 + 6x = 2x(x - 1)(x - 3).

Without an equality sign the given terms can't be considered to be an equation

x3 + 7x = 8x2x3 + 7x - 8x2 = 0 [subtract 8x2 from both sides]x(x2 + 7 - 8x) = 0 [factor out x]x(x-1)(x-7) = 0 [factor]Since the product of the three factors x, x-1, and x-7 equals zero, any of the three expressions could equal zero:x = 0x - 1 = 0, x = 1x - 7 = 0, x = 7Therefore, there are three solutions to the equation x3 + 7x = 8x2:x = 0x = 1x = 7Or, in set notation: x = {0,1,7}

8x2(x + 3)

(2x + 1)(4x + 7)

Once you simplify it, it will become 9x2+5x+40. And, that should make it a little easier. I'm afraid I'm no help after that... hope it helps! :)Further Information:-This quadratic espression can't be factored because its discriminant is less than zero.

8 and 2 8x2=16